IMPLEMENTASI METODE MULTYFACTOR EVALUATION PROCESS (MFEP) PEMBERIAN PENGHARGAAN DESA BERSINAR - Mia Amelya Lubis (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
BERSINAR Village is one of the efforts to prevent and handle drug abuse in the village which is managed independently by the village government together with the village community. In determining the shining village award, a system is needed that can provide effective decisions. The Multifactor Evaluation Process (MFEP) method is one method that can be used in a decision support system. By using the MFEP method, each predetermined criterion is given a weighting according to its needs. Then each alternative is evaluated based on these factors. The alternative with the highest score is the solution in choosing the village that deserves the award. The MFEP method in making this decision uses the Visual Basic 2010 programming language and the MySQL database. So that the application can be used to assist the BNN in making decisions on selecting villages that are entitled to the Shining village award